SOME VECTOR FIELDS ON A RIEMANNIAN MANIFOLD WITH SEMI-SYMMETRIC METRIC CONNECTION - (:unkn) unknown (IRANIAN MATHEMATICAL SOC, 2012)
In the first part of our work, some results are given for a Riemannian manifold with semi-symmetric metric connection. In the second part, some special vector fields, such as torse-forming vector fields, recurrent vector fields and concurrent vector fields are examined in this manifold. We obtain some properties of this manifold having the vectors mentioned above.
Keywords: Semi-symmetric metric connection; torse-forming vector field; recurrent vector field; concurrent vector field; SPACES